Functional Movement Screen Differences in Male and Female Footballers and as an Injury Prevention Tool : Functional Movement Screen Differences - Amjad, Fatima; Latif, Danish; Hanif, Sana; Bashir, Kiran; Batool, Rubia; Khalid, Uzair (Pakistan Journal of Health Sciences, 2023)
Functional Movement Screen evaluates seven key movement tasks crucial for smooth kinetic chain performance in sports. It assists sports therapists and coaches in identifying faulty patterns during preparticipation. Objectives: To compare FMS composite scores between male and female footballers and evaluate FMS as an injury predictor tool. Methods: Between March and June 2021, a cohort study was conducted on 264 footballers (132 males and 132 females) in Islamabad and Rawalpindi football academies. Players voluntarily underwent seven Functional Movement Screen tests. After participating in competitive or friendly matches, follow-ups were conducted to assess FMS composite scores and document any injuries sustained during the games. Data analysis was performed using SPSS 25.0, and information on FMS scores and injuries was collected through FMS scoring sheets and a self-structured questionnaire. Results: There was statistically significant difference between male and female footballers composite scores of FMS (p<0.005). Female footballers (15.13 ± 2.32) scored less on mean score of FMS as compared to male footballers (17.03 ± 2.884). FMS was a good predictor of injury with 37.7 % variance on linear regression (p=0.005). Conclusions: Female footballers scored less composite score of FMS as compared to male footballers. FMS before participation can be a good predictor for detecting injuries in male and female footballers.